STUDI LITERATUR: PENGGUNAAN METODE ACTIVITY-BASED COSTING DALAM MEMBEBANKAN BIAYA OVERHEAD PABRIK PADA COST OBJECTIVE - Cindy Vinella; Maria Ellita Ovina; Hanif Hanif (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
This study aims to analyze how to use the activity-based costing method in calculating production overhead costs. This study uses a Systematic Literature Review (SLR) approach. The research period in the selected journal sample is 2015-2022 with a sample of 40 journals to review with the theme of activity-based costing. The results of this study indicate that from year to year, there are more and more research themed activity-based costing with a scope of 30 national journals and 10 international journals. That journals with the topic of activity-based costing and cost of goods manufactured are the most popular with a total of 20 journals. The most widely used method is descriptive qualitative method. Several formulas are used to calculate the overhead costs, cost of goods manufactured, selling price per unit, and profitability. There is a difference in the calculation between using the activity-based costing method and other methods such as volume-based costing and time-driven activity-based costing. In addition, indirect costs, market competition, and product diversification affect the decision-making whether using the activity-based costing method or not